Association of lifestyle behaviors with non-alcoholic fatty liver disease and advanced fibrosis detected by transient elastography among Hispanic/Latinos adults in the U.S. Issue 2 (17th February 2023) - Heredia, Natalia I.; Zhang, Xiaotao; Balakrishnan, Maya; Hwang, Jessica P.; Thrift, Aaron P.
ABSTRACT: Objectives: Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent liver disease, with the highest prevalence observed in the U.S. among Hispanic/Latino adults. While physical activity and dietary behaviors have established protective associations with NAFLD and its severity, these associations have not been well-characterized in Hispanic/Latino adults. The purpose of this study was to assess the association of lifestyle behaviors with NAFLD and advanced fibrosis in US Hispanic/Latino adults. Design: We selected all Hispanic/Latino adults from the 2017–2018 National Health and Nutrition Examination Survey (NHANES). NAFLD was defined as CAP ≥285 dB/m, and advanced fibrosis as liver stiffness measurements ≥8.6 kPa. Multivariate-adjusted logistic regression models assessed associations of physical activity and sedentary behavior (Global Physical Activity Questionnaire), as well as diet quality (Healthy Eating Index [HEI]-2015) and total energy intake (24-hour recall) with NAFLD and advanced fibrosis. Results: In Hispanic/Latino adults, the overall prevalence of NAFLD was 41.5%, while the prevalence of advanced fibrosis among those with NAFLD was 17.2%. We found that higher levels of physical activity and high diet quality were associated with lower risk of NAFLD. Compared to those reporting on average 0 metabolic equivalent (MET) hours/week of physical activity, participants reporting high levels of physical activity (≥32 MET hours/week) had 40% lower risk of NAFLD (Adjusted OR = 0 .60, 95%CI 0.38, 0.93). High diet quality (HEI-2015) was associated with a 30% lower risk of NAFLD (Adjusted OR = 0 .70, 95% CI 0.51, 0.97) and 72% lower risk of advanced fibrosis (Adjusted OR = 0 .28, 95% CI 0.12, 0.66), as compared to those with low diet quality. Conclusions: In this population-based study, high levels of physical activity and diet quality were associated with lower risk of NAFLD in Hispanic/Latino adults. Public health and medical professionals need to concentrate efforts on lifestyle behavior change in Hispanic/Latino adults who are at high risk for serious liver disease.